2000
DOI: 10.1046/j.1464-410x.2000.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of rat bladder and urethra: evaluation of urinary and reproductive function after inducing protoporphyrin IX with 5‐aminolaevulinic acid

Abstract: Objective To assess the urinary and reproductive function of rats after inducing protoporphyrin IX with 5-aminolaevulinic acid (ALA) and subsequent intraurethral photodynamic therapy (PDT). Materials and methods Twelve female Wistar rats were given ALA orally or intravesically (four each), followed by intraurethral PDT through a 10-mm cylindrical ®bre at 100 mW for 500 s (argon laser, 632 nm). Urinary frequency, the number of gestations and histological changes were then evaluated and compared with a group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…30,31 Our data also provide the basis for planning combination PDT and chemotherapy, as in preliminary in vitro studies, 32 since different mechanisms of toxicity can be combined in a defined manner to optimize the ratio between toxicity and side effects. These data may be used to enhance differential photodynamic effectiveness between tumor and normal cells in clinical PDT, thus avoiding negative side effects.…”
Section: Discussionmentioning
confidence: 89%
“…30,31 Our data also provide the basis for planning combination PDT and chemotherapy, as in preliminary in vitro studies, 32 since different mechanisms of toxicity can be combined in a defined manner to optimize the ratio between toxicity and side effects. These data may be used to enhance differential photodynamic effectiveness between tumor and normal cells in clinical PDT, thus avoiding negative side effects.…”
Section: Discussionmentioning
confidence: 89%
“…assessed the urinary and reproductive function of rats after inducing PpIX with ALA and subsequent intraurethral PDT. The results showed that PDT of the urethra with ALA is relatively safe and carries few risks of inducing permanent urological complications 12 …”
Section: Discussionmentioning
confidence: 94%
“…The results showed that PDT of the urethra with ALA is relatively safe and carries few risks of inducing permanent urological complications. 12 This is the first study reporting on the efficacy of ALA-mediated PDT of urethral condylomata. In this study, 156 of 164 achieved complete response after one to four treatment cycles.…”
Section: Discussionmentioning
confidence: 98%
“…Fig. 3 shows urethral length (8,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and diameter (15,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), flow rate (35)(36)(37)(38)(39)(40)(41)(42), bladder capacity (25,(43)(44)(45)(46)(47)(48)(49), and bladder pressure (1,35,39,40,43,46,50) for over 100 individuals across 13 species.…”
Section: Resultsmentioning
confidence: 99%
“…To predict the flow speed of a rat, inputs to this equation include the rat's bladder pressures and urethral anatomy (15,16,50) (P bladder = 6.03 kPa, L = 20 mm, D = 0.8 mm).…”
Section: Steady-state Equation Ofmentioning
confidence: 99%